Injecting New Workforce Leaders in Tourism, Hospitality and Environmental Science: A Community-Engaged Learning and Immersion Class - Michaud, Tracy; Sanford, Robert (Maine Policy Review, 2018)
Tourism, especially nature-based tourism, is a major and growing industry in Maine. Therefore, it is important that colleges and universities graduate leaders into the Maine workforce with specific knowledge of the tourism and hospitality industry and with a connection to the environment in which it is flourishing. To graduate these potential leaders, schools must do a better job at retaining and graduating students from diverse socioeconomic backgrounds. Community-engaged learning, including immersion classes, are a key strategy to increase student persistence in some programs at the University of Southern Maine (USM). Two academic units at USM, the Program in Tourism and Hospitality and the Department of Environmental Science and Policy, collaborate in delivering a colocated intensive immersion class for all new majors. This engagement early in their college career fosters a sense of community among the students and with the industry in which they will work. We argue that this community engagement is a factor contributing to student retention and success in these programs and will help create the creative, resilient, locally active leaders needed to guide sustainable tourism development in Maine.
Keywords: tourism industry; hospitality industry; Maine; student retention; University of Southern Maine